Load-Induced Changes of Inter-Limb Asymmetries in Dynamic Postural Control in Healthy Subjects - Heil, Jessica (Frontiers in Human Neuroscience, 2022)
Inter-limb asymmetries are associated with a higher potential risk for non-contact injuries. Differences in function or performance between the limbs might lead to imbalances and promote instability, increasing the potential risk for injuries. Consequently, an investigation of inter-limb asymmetries should be included in injury risk assessment. Furthermore, since non-contact injuries mainly occur under loaded conditions, an investigation of load-induced changes of inter-limb asymmetries can provide additional information on the athlete’s potential injury risk. Therefore, the current study aimed to investigate the influence of physical load on inter-limb asymmetries in dynamic postural control, which is essential in situations with a high risk for non-contact injuries such as landing, cutting, or stopping. In total, dynamic postural control of 128 active and healthy subjects (64 males and 64 females, age: 23.64 ± 2.44, height: 176.54 ± 8.96 cm, weight: 68.85 ± 10.98 kg) was examined. Dynamic postural control was tested with the Y-Balance Test before and after a loading protocol on a bicycle ergometer or a treadmill. The results showed no statistically significant increase of the inter-limb asymmetries in anterior direction (F1, 126 = 4.44, p = .04, η2p = .03). Moreover, there is high variation between the subjects regarding the magnitude and the direction of the asymmetries and the changes due to load. Therefore, a more individual analysis considering the magnitude and the direction of the asymmetries is required. Thereby, considering different modifying factors, e.g., sex, injury history, and baseline level of asymmetries, can be helpful. Moreover, an analysis of the changes during load might provide further insights, reveal possible differences, and help detect the reasons and mechanisms underlying inter-limb asymmetries and asymmetrical loading.